Myrtucommulone‐A Induces both Extrinsic and Intrinsic Apoptotic Pathways in Cancer Cells. Issue 9 (2nd June 2015) - Izgi, Kenan; Iskender, Banu; Jauch, Johann; Sezen, Sedat; Cakir, Mustafa; Charpentier, Maël; Canatan, Halit; Sakalar, Cagri
ABSTRACT Myrtucommulone‐A is the active compound derived from Myrtus communis. The molecular targets of myrtucommulone‐A is widely unknown, which impedes its potential therapeutic use. In this study, we demonstrated the cytotoxicity of MC‐A and its potential to induce apoptosis in cancer cells. Myrtucommulone‐A was also found to be antiproliferative and strongly inhibited cancer cell migration. Eighty four apoptotic pathway genes were used to assess the effect of myrtucommulone‐A on cancer cells. Myrtucommulone‐A mediated an increase in apoptotic genes including Fas, FasL, Gadd45a, Tnf, Tnfsf12, Trp53, and caspase 4. The increase in myrtucommulone‐A dose (25 μM versus 6.25 μM) also upregulated the expression of genes, which are involved mainly in apoptosis, regulation of apoptosis, role of mitochondria in apoptotic signaling, cytokine activity, and tumor necrosis factor signaling. Our data indicate that myrtucommulone‐A could be utilized as a potential therapeutic compound with its molecular targets in apoptotic pathways.